Analysis of Biomass Potential and Carbon Stocks on Various Vegetation Types in Trembesi City Forest and Putroe Phang City Forest in Banda Aceh - Fadhilah Harahap; Sufardi Sufardi; Halim Akbar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Urban forests play an important role in climate change mitigation by storing biomass and carbon. This study aims to analyze the potential of biomass and carbon stocks in various types of vegetation in the Trembesi City Forest and Putroe Phang City Forest in Banda Aceh. The study uses a quantitative descriptive approach through vegetation inventory, employing non-destructive sampling methods. Field data in the form of tree type, number of individuals, and trunk diameter are used to calculate biomass using allometric equations, then converted into carbon stocks. The results of the study show that the Trembesi City Forest has a higher biomass potential and carbon reserves than the Putroe Phang City Forest. This is influenced by the dominance of large-diameter, wide-headed trees, which contribute significantly to biomass accumulation. In contrast, the Putroe Phang Urban Forest has a more diverse vegetation structure, but is dominated by medium-sized trees, resulting in relatively lower biomass potential and carbon reserves. The findings of the study confirm that the size of the diameter of the tree is a major factor in determining the amount of biomass and carbon reserves. Thus, the presence of large trees in urban forests plays a strategic role in improving the area's ecological function as a carbon store and supporting the sustainability of the urban environment. Keywords: Biomass, Carbon Reserves, Urban Forests, Vegetation, Banda Aceh.